Hubungan kualitas air terhadap ikan Saluang (Rasbora sp) di danau Lutan kota Palangka Raya - Ummi Suraya (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
The research was conducted to analyzed the growth and abundance of Saluang Fish (Rasbora sp) and to know the relationship between water quality and seluang fish in lake Lutan, Palangka Raya. The research was carried out from july to september 2015. The samples of Saluang fish were collected using gill net. According to the analysis of the relationship between length-weight fish saluang showed the natural growth of saluang fish was allometrik. The fluctuation of water depth influenced water like temperature, muddiness; brightness, degrees of acidity (pH) and dissolved oxygen (DO). The variables of water quality which had significant effect on the dynamics of saluang fish in lake Lutan were water depth and brightness.